THE THERAPEUTIC APPROACH OF YOUNG PATIENTS, STUDENTS, WITH SOCIAL ORAL PATOLOGY AND THE ASSOCIATED THERAPY IN MENTAL HEALTH CONDITIONS - Laura Elisabeta Checherita; Vasilica Toma; Ovidiu Stamatin; Costin Iulian Lupu; Liana Aminov; Magda Cuciureanu; Sorina Mihaela Solomon; Silvia Teslaru; Laurian Francu; Carina Ana Maria Balcos; Tudor Hamburda; Armencia Oana Adina; et al. (Romanian Society of Oral Rehabilitation, 2023)
The current study intends to highlight the relationship and, at times, the influence between anxiety disorders and dental dysfunctional syndromes of stomatognathic system(SDSS) in young students from our institution : Basis Of The Dental Care Clinic ,,Mihail Kogalniceanu,, Iasi. These are involved in various stressful intellectual activities and have identified a complex health problem that needed to be solved in light of the constant stress that the present time offers, laying the foundations for a focused and direct approach that will increase the certainty of growth. the quality of life. Be the way, the types of young social cases will be able to be solved, and will gather an extent of the accessible tools and skills. We also rely on the acquisition of skills through the experience conferred in this study to offer optimal solutions in these clinical situations.